Pengaruh Kualitas Audit, Kepemilikan Manajerial Dan Kompensasi Bonus Terhadap Manajemen Laba Dengan Variabel Kontrol Profitabilitas, Leverage Dan Ukuran Perusahaan - Maulina, Thalia Rizky; Pratomo, Dudi (eProceedings of Management, 2024)
Earnings management is a manager's effort to influence financial report information by increasing or reducingprofits for his own benefit. This causes the company's financial reports to not reflect actual conditions. This causesthe company's financial reports to not reflect actual conditions. This paper aims to determine the effect of auditquality, managerial ownership, and bonus compensation on earnings management. The population in this studyare infrastructure sector companies listed on the Indonesia Stock Exchange for the 2018 - 2022. The sample wasdetermined using a purposive sampling technique and obtained 65 samples, consisting of 13 companies with aresearch period of 5 years. The analysis technique used is panel data regression analysis using EViews 12software. The results of this research show that the variables audit quality, managerial ownership, and bonuscompensation simultaneously influence earnings management. Partially, the audit quality variable has asignificant negative effect on earnings management. Bonus compensation has a significant positive effect onearnings management. Meanwhile, the managerial ownership variable has no significant effect on earningsmanagement. Keywords-earnings management, audit quality, managerial ownership, bonus compensation, profitability,leverage, company size